Resistansi Tradisi Kitab Kuning Pada Madrasah Al-Washliyah di Sumatera Utara - Muhammad Riduan Harahap; Saiful Akhyar Lubis (UMSU, 2019)
Resistance of the tradition of learning the yellow book in the Al Washliyah madrassas departs from the following epistemological thoughts; (a). Thoughts about the primacy of religious knowledge (b). Mastery of the Yellow Book as the Main Criteria for Ulama, (c). Whereas the yellow book as part of the Al Washliyah sibgah (characteristic); (d). The consequences of self-engagement in the Ahl al-Sunnah Wa al-Jamâ'ah and the Shafi'i school of thought; and (e). Thoughts of belief in the results of the previous Ijtihad scholars. The effort to resist the tradition of learning the yellow book in the Al Washliyah madrassas is; (a). Efforts to silence religious science subject matter (b). The occurrence of a crisis of scholars; (c). Emerging and increasingly developed schools of thought or religious notions; and D). There is a negative impact on the development of internet technology. The forms of resistance in the tradition of book learning in the Al Washliyah madrasa are various, namely; (a) Consistently maintaining Al Washliyah's 100% diniyah curriculum and refusing to apply the Department of Religion curriculum; (b). Modifying the curriculum, where the Al Washliyah madrasa accepts the Department of Religion curriculum, but by manipulating teaching materials / materials in the field; (c) Implement learning by combining Al Washliyah's diniyah curriculum and the Department of Religion's curriculum with a proportion of 70% of the diniyah curriculum and 30% of the Department of Religion's curriculum, as well as in other madrasas the ratio is 50% curriculum of diniyah and 50% of the Department of Religion's curriculum; (d). Develop extracurricular programs